Die chronische Epicondylopathia humeri radialis: Operation nach Nirsch = Chronic lateral epicondylitis : the Nirschl procedure - Müller, Axel; Spies, Christian; Unglaub, Frank; Bruckner, Thomas; Pötzl, Wolfgang (Operative Orthopädie und Traumatologie, 2015)
PurposeReduction of burden insufficiency.IndicationChronic lateral epicondylitis.ContraindicationsAcute infection in the surgical area. C6/7 nerve root and plexus irritation. Frohse Arcade syndrome. Posterolateral rotatory instability.Surgical techniqueIncision slightly cranial to the radial epicondyle. Identification of the extensor carpi radial brevis tendon (ERCB) and longus (ECRL). Mobilisation of the ECRL tendon, identification of degenerative tendons of the ECRB. Excision of degenerative tissue. Drill holes in the area of the smoothed radial epicondyle, thermal denervation.Postoperative managementArm plaster splint for 14 days. Unrestricted activity after 4-6 weeks. Maximum loading after 6 months.ResultsOf the 24 consecutively operated patients, 83.3 % were included. High patient satisfaction. Nirschl tennis and elbow score improved from 35 to 75 points postoperatively. Pain levels decreased from 6.8 to 1.4 points postoperatively.
Gesehen am 17.10.2017